Karyotype analysis of Baguio leeks, allium porrum L. (Alliales Alliaceae). - Sorilla, Richie A.
Karyotype analysis of C-metaphase chromosomes spreads from mitotic root tip cells of `Baguio leeks,' Allium porrum L. showed a somatic chromosome number of 2n=14. The complement consisted of 4 long and 10 short diploid chromosomes that were further categorized into 3 groups: 2 sm type chromosomes possessing submedian centromeres; 2 st type chromosomes having subterminal centromeres; and 10 m type chromosomes with median centromeres. Mitotic index for the species was noted at 14.58.